Hubungan Motivasi dan Produktivitas Kerja Buruh Sadap Karet Kebun Banjarsari PTPN XII di Kecamatan Bangsalsari Kabupaten Jember - Ahmad Rofii; Evita Soliha Hani (Fakultas Pertanian Universitas Jember, 2020)
Rubber tapping workers are piece workers in which these workers receive wages based on the volume of work or units of work. One of the plantation companies managed by BUMN is PTPN XII. One of the gardens that was the highest revenue contributor for the company was the PTPN XII Banjarsari Garden in Bangsalsari District, Jember Regency. The problem that often arises in piece workers such as rubber tapping workers is the problem of wages. The productivity of the rubber tapping workers affects the wages earned by the rubber tapping workers. Research at the Banjarsari Plantation of PTPN XII, aims to determine: (1) The work motivation of PTPN XII's Banjarsari rubber tapping laborers, (2) The work productivity of PTPN XII's Banjarsari rubber tapping workers in, (3) The relationship between work motivation and work productivity of rubber tapping laborers in the Banjarsari Plantation of PTPN XII. The results of the analysis show that: (1) The level of work motivation of rubber tapping workers at Banjarsari Plantation PTPN XII is high, (2) The productivity level of rubber tapping workers at Banjarsari Plantation PTPN XII is high, (3) There is a significant and unidirectional relationship between motivation. and labor productivity of rubber tapping at PTPN XII's Banjarsari Plantation. Keywords: Rubber Tapping, Motivation, Productivity, Relationship between work motivation and work productivity